Fully-controllable PWM for SPMC with bi-directional operations / Mohd Asyraf Rongi - Rongi, Mohd Asyraf (2015)
Dependency on bulky external hardware, high memory bits consumption for generating digital control signals, and the lack of flexibility to control the SPMC (Single Phase Matrix Converter) are of major concerns. Thus the focuses of this research are to further optimize the whole SPMC system to be more compact and portable with less dependency on external hardware, to design a digital control signal generator module with much lesser memory bits consumption, and to develop a fiilly controllable control signals that can fully control the SPMC for bi-directional operations which are AC to DC (rectifier) and DC to AC (inverter) operations. Firstly, literature review on the previous work, as well as studies on FPGA (Field Programmable Gate Array) and SPMC hardware was done. Followed by simulation works using ModelSim for digital control signal generator modules’ output simulations, as well as using Matlab Simulink (MLS) for SPMC’s R-load voltage and R-load current output simulations. When simulations results are consistent with theoretical readings, hardware experiments were conducted including the use of Altera DE2-70 FPGA board and real SPMC hardware. Experiment results were then compared with simulation results for performance and consistency checking. Major findings include the use of CORDIC (COmputer Rotation Digital Computer) to replace the Look-Up Table (LUT) method for generating one of the control signals, resulting in much reduced memory bits usage. Also by fully utilization the Altera DE2-70 FPGA board, control signals can be fully adjusted and controlled without the need of external hardware equipments.